Immune Thrombocytopenic Purpura following Administration of mRNA-Based SARS-CoV-2 and MMR Vaccinations: A Cautionary Tale - Whitney Thomas; Adam Albano; Dean Kirkel; Nason Rouhizad; Folasade Arinze (Case Reports in Infectious Diseases)
We report a case of immune thrombocytopenic purpura (ITP) in an otherwise healthy 31-year-old man following coadministration of the live measles, mumps, and rubella (MMR) vaccine with the Pfizer-BioNTech mRNA SARS-CoV-2 vaccine. The patient was hospitalized briefly and treated for ITP with glucocorticoids, IVIG, and platelet transfusion. Although our patient’s clinical presentation and subsequent course are similar to those of other cases of ITP in association with SARS-CoV-2 vaccination, to our knowledge, this is the first reported case of ITP following MMR and mRNA SARS-CoV-2 vaccine coadministration. It would be impossible to conclusively prove that the patient’s thrombocytopenia was secondary to the SARS-CoV-2 vaccine alone, the MMR vaccine, or an additive effect of both vaccines. However, with the CDC guidelines recommending the coadministration of the mRNA SARS-CoV-2 vaccine without regards to timing with other vaccines, we urge further caution as there is limited evidence to inform practice. This case highlights the need for further safety data regarding the coadministration and timing of the mRNA SARS-CoV-2 vaccine with other vaccines.